Preface to the Special Issue in Memory of Prof. Jiequan Li (Communications in Computational Physics, 2026)
Preface to the Special Issue in Memory of Prof. Jiequan Li, published in Communications in Computational Physics, Vol. 39, No. 5, May 2026.